Book review of: Phillimore, Jenny; Bradby, Hannah; Brand, Tilman; Padilla, Beatriz; Pemberton, Simon (2021): Exploring Welfare Bricolage in Europe’s Superdiverse Neighbourhoods - Nessler, Miriam (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Book review.